What should guide our patient management of vulvovaginal atrophy?. (2nd January 2019) - Shapiro, M.
Abstract: Genitourinary syndrome of menopause including vulvovaginal atrophy is commonly experienced by postmenopausal women, reducing their quality of life. The aim of this review is to assess current treatment options within the framework of recent management guidelines. Recommendations include use of treatments addressing both symptoms and the underlying pathophysiology, and proactive patient discussion. Both prescription and non-prescription options are recognized, including non-hormone-based approaches. Local therapy is preferable in the primary treatment of genitourinary syndrome of menopause symptoms as risk of adverse events is reduced, although long-term safety data are limited. Management of patients with a history of breast cancer requires careful consideration, although estrogen therapy has not been associated with increased risk of breast cancer or of recurrence. Treatment should consider ongoing cancer therapy. As multiple, comparable options exist, treatment choice may be due to experience and patient preference. Best management requires effective patient–physician communication and shared decision-making.